Klasifikasi Resting-State Dan Task-State Pada Functional Magnetic Resonance Imaging Menggunakan Cross Correlation dan Support Vector Machine - Agus Eko Minarno (Jurnal Gamma, 2014)
Klasifikasi Resting-State Dan Task-State Pada Functional Magnetic Resonance Imaging Menggunakan Cross Correlation dan Support Vector MachineClassification of Resting-State and Task-State In Functional Magnetic Resonance Imaging Using Cross Correlation and Support Vector MachineAgus Eko MinarnoJurusan Teknik Informatika, Fakultas Teknik, Universitas Muhammadiyah MalangJl. Tlogomas 246 Malang (0341) 464318 Email : agoes.minarno@gmail.com ABSTRACTIn the previous study identified several overlapping voxel during the resting-state and state task. Methods for determining the connectivity map involves overlapping areas, less than optimal in describing patterns of task-state as a feature. In this study, proposed a new method for the selection of features to improve accuracy and reduce computational time in determining significant voxel-state task when using a non-overlapping area. Selection of the features to determine significant voxel using cross Correlation, and take voxel correlation value which is above the average correlation. The next stage is the determination of the threshold value to determine the number of voxels are chosen as a feature. The selected features will be labeled in accordance with the given stimulus, namely picture and sentence, and then selected voxel to obtain non-overlapping between the stimulus picture with the stimulus sentence. The average yield of 6 subjects, methods that involve overlapping area using SVM classifier obtained precision, recall, and accuracy respectively 94.2%, 95.1%, 94.6% and computation time 0.021 seconds. While the method has a non-overlapping area of precision, recall, and accuracy respectively 95.0%, 95.3%, 95.1% and computation time 0.019 seconds. Feature selection methods using non-overlapping area has the accuracy and computation time better than methods that involve overlapping area, in determining the connectivity map.Keywords: feature selection, task-state, cross-correlation, voxel-based selection, non-overlappingABSTRAKPada penelitian sebelumnya teridentifikasi beberapa voxel yang overlapping pada saat resting-state dan task state. Metode untuk menentukan connectivity map melibatkan daerah yang overlapping, kurang optimal dalam menggambarkan pola task-state sebagai ciri. Pada penelitian ini, diusulkan sebuah metode baru untuk pemilihan fitur untuk meningkatkan akurasi dan mengurangi waktu komputasi dalam menentukan voxel yang signifikan pada saat task-state menggunakan metode non-overlapping area. Pemilihan fitur untuk menentukan voxel yang signifikan menggunakan cross corelation, dan mengambil voxel dengan nilai korelasi yang berada diatas korelasi rata-rata. Tahapan berikutnya adalah penentuan nilai ambang batas (threshold) untuk menentukan jumlah voxel yang dipilih sebagai fitur. Fitur yang terpilih akan diberi label sesuai dengan stimulus yang diberikan, yaitu picture dan sentence, kemudian diseleksi untuk mendapatkan voxel yang non-overlapping antara stimulus picture dengan stimulus sentence. Hasil rata-rata dari 6 subyek, metode yang melibatkan overlapping area menggunakan classifier SVM diperoleh precision, recall, dan accuracy masing–masing 94.2%, 95.1% , 94.6% dan waktu komputasi 0.021 detik. Sedangkan metode non-overlapping area memiliki precision, recall, dan accuracy masing–masing 95.0%, 95.3% , 95.1% dan waktu komputasi 0.019 detik. Pemilihan fitur menggunakan metode non-overlapping area memiliki akurasi dan waktu komputasi yang lebih baik dari metode yang melibatkan overlapping area, dalam menentukan connectivity map.Kata kunci : feature selection, task-state, cross-correlation, voxel-based selection, non-overlapping